Strategi Pemasaran Dalam Meningkatkan Penjualan Sepatu Pada Home Industry Yap Yek Di Kota Bukittinggi: Strategi Pemasaran Dalam Meningkatkan Penjualan Sepatu Pada Home Industry Yap Yek Di Kota Bukittinggi - Nurfitriyenni, Nurfitriyenni (Jurusan PIPS FKIP UMMY Solok, 2021)
The purpose of this study was to determine the chosen marketing strategy in increasing shoe sales at Yap Yek Home Industry in Bukittinggi. Technical analysis of data using the SWOT method, namely analysis of the factors of strength (strength), as well as knowing weaknesses. Meanwhile, analysis of external factors must be able to determine the opportunity (opportunity), and also know the threat (treat) by filling out a questionnaire. After that, these factors are analyzed using the IFE matrix, EFE matrix, SWOT matrix, and weight-score table analysis. Based on the results of the study, it can be concluded that the marketing strategy used by Yap Yek's home industry with the highest total weight score on the Strenghts-Opportunities (S-O) strategy is 3.87. By optimizing the strength to take advantage of existing opportunities. Namely maintaining and improving product quality to attract new customers and retain existing customers, making constant innovations in products, especially in design and color to attract more consumers to use shoe products, maximizing marketing of owned leather shoe products, especially during the holiday season, following every major events and events such as the exhibition of industrial products by providing a bigger discount. Keywords: Marketing Strategy, Sales, SWOT Analysis.